Is This the End? Lifetime of Electrical and Electronic Equipment - Sahin, Betul; Clark, Nikki; Lilley, Debra (Proceedings of the 6th Product Lifetimes and the Environment Conference (PLATE2025), 2025)
The rapid advancement of technology, coupled with global digitalisation and the growing demand for innovative consumer electronics, has led to a dramatic increase in the production and consumption of electrical and electronic equipment (EEE). This trend has raised significant concerns regarding the sustainability of EEE usage, particularly in terms of their obsolescence, disposal, and environmental impact. Addressing these concerns, this study surveyed 600 undergraduate students, who reported on 14 different types of EEE, to explore the reasons for obsolescence (RQ1), the most common methods of managing obsolete devices based on their types (RQ2), and students’ awareness of alternative waste management methods (RQ3). Results were reported using frequencies and percentages. Findings reveal that obsolescence is mainly driven by “broken beyond repair,” “worn-out technology,” “outdated technology,” and “lack of required functions,” indicating that absolute and technical obsolescence are the primary factors. The most common way of dealing with obsolete devices is to “keep it” across all device types, with “throwing away” emerging as another frequent method for electrical devices. More than half of the students are aware of accessible alternatives, such as “online sales” and “charity donations,” though irregular or infrequent options tend to have lower awareness levels. This study highlights the behavioural trends and gaps in awareness among students regarding EEE obsolescence and disposal, emphasising the importance of promoting sustainable practices and raising awareness about accessible waste management alternatives.